Insight into the global evolution of Rodentia associated Morbilli-related paramyxoviruses - Wissem Ghawar (Nature Portfolio, 2017)
Abstract One portion of the family Paramyxoviridae is a group of Unclassified Morbilli-Related Viruses (UMRV) recently recognized in wild small mammals. At a global level, the evolutionary history of these viruses is not properly understood and the relationships between UMRV and their hosts still remain largely unstudied. The present study revealed, for the first time, that Rodentia associated UMRV emerged from a common ancestor in southern Africa more than 4000 years ago. Sequenced UMRV originating from different regions in the world, clustered into four well-supported viral lineages, which suggest that strain diversification occurred during host dispersal and associated exchanges, with purifying selection pressure as the principal evolutionary force. In addition, multi-introductions on different continents and islands of Rodentia associated UMRV and spillover between rodent species, most probably Rattus rattus, were detected and indicate that these animals are implicated in the vectoring and in the worldwide emergence of this virus group. The natural history and the evolution dynamics of these zoonotic viruses, originating from and hosted by wild animals, are most likely shaped by commensalism related to human activities.